Pengaruh Good Corporate Governance Pada Nilai Perusahaan Dengan Moderasi Corporate Social Responsibility - Prastuti, Ni Ketut Karlina; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 13 No 1 (2015), 2015)
One of the long-term goals to be achieved by a company is a high increase in the value of the company. There are several factors that can affect the value of the company, one of them is good corporate governance (GCG). The purpose of this study was to determine the effect of good corporate governance (which proxied by managerial ownership, institutional ownership, the proportion of board of directors, and audit committee ) on the value of the company, and whether the relationship of good corporate governance with firm value can be moderated by the Corporate Social Responsibility .This studi using mining companies in Indonesia Stock Exchange of 2009 – 201 3 , which purposive sampling method . As t he method of analysis this study using multiple linear regression and regression moderation. T his study found institutional ownership and audit committee have a negative effect on the firm value , w hile the variable s proportion of managerial ownership and board of commissioners ha ve no effect on firm value. Disclosure of corporate social responsibility can’t be able to moderate the effect of corporate governance on firm value.
Keywords: corporate governance, firm values, corporate social responsibility